Applicability of Pragmatism in the Implementation of the 9-3-4 System of Education in Nigeria - Ategwu, Emeka (NIU Journal of Humanities, 2022)
The study closely examined the historical purview of the concept of pragmatism, discussed the central ideas inherent in this school of thought, x-rayed the evolution of the present system of education in Nigeria, and presented in a nutshell the relevance of pragmatism in this system. Finally, the study suggested further measures for the appropriate applicability of this school of thought towards the improvement of the overall educational system and societal advancement.